Classification of Fracture Risk in Fallers Using Dual‐Energy X‐Ray Absorptiometry (DXA) Images and Deep Learning‐Based Feature Extraction - Damith Senanayake; Sachith Seneviratne; Mahdi Imani; Christel Harijanto; Myrla Sales; Peter Lee; Gustavo Duque; David C. Ackland (JBMR Plus, 2023)
Abstract Dual‐energy X‐ray absorptiometry (DXA) scans are one of the most frequently used imaging techniques for calculating bone mineral density, yet calculating fracture risk using DXA image features is rarely performed. The objective of this study was to combine deep neural networks, together with DXA images and patient clinical information, to evaluate fracture risk in a cohort of adults with at least one known fall and age‐matched healthy controls. DXA images of the entire body as, well as isolated images of the hip, forearm, and spine (1488 total), were obtained from 478 fallers and 48 non‐faller controls. A modeling pipeline was developed for fracture risk prediction using the DXA images and clinical data. First, self‐supervised pretraining of feature extractors was performed using a small vision transformer (ViT‐S) and a convolutional neural network model (VGG‐16 and Resnet‐50). After pretraining, the feature extractors were then paired with a multilayer perceptron model, which was used for fracture risk classification. Classification was achieved with an average area under the receiver‐operating characteristic curve (AUROC) score of 74.3%. This study demonstrates ViT‐S as a promising neural network technique for fracture risk classification using DXA scans. The findings have future application as a fracture risk screening tool for older adults at risk of falls. © 2023 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.